Power quality issues in South America: Presentt reality and future opportunities - Arruda, A.; Brasil, D.; Issouribehere, P.; Torres, M.T.; Rios, S.M.; Ribeiro M. Samotyj, P. (Revista de Ingeniería, 1995)
The objective of this paper is to present an overview of the power quality industry and issues in South America. An attempt is made to focus on the present needs and future opportunities for R&D and international cooperation. The paper reveals aspectos of the tends, efforts, solutions and insights progressinf in South American countries coping with power quality in the context of political, economical and organizational structures. Form the impact of pioneering transmission access on power quality, to developing instrumentation and standards, to national surveys, a broad spectrum of experience is presented in this paper.